Investigation on the Flow Behaviour of Agar Solution and Rheological Modelling - Karataş, Mukaddes (My University, 2023)
In this study, the effect of shear rate, agar concentration (15-35 kg/m3) and temperature (30-60°C) on the apparent viscosity of the agar solution was investigated. Apparent viscosities at different shear rates were determined using a rotational viscometer. The findings show that the apparent viscosity decreasing with a rise of shear rate increased with increasing concentration. An increase in the tempearture, on the other hand, led to a decrease in the apparent viscosity. To illustrate both temperature and concentration changes together, the Bingham, power law, and Casson models were utilized in choosing the most suitable model. When the models were compared using statistical tests, the most compatible model was found to be the power-law model. The consistency coefficient and flow behaviour index calculated using the power law model showed that agar solutions exhibited shear-thinning flow behavior (pseudoplastic). This study suggests that power law, within the ranges of the temperature and concentration studied could be used to estimate the viscosity of the agar solutions in the applications requiring the knowledge of flow behavior.
Keywords: Flow behaviour; Rheological models; Agar-agar; Rotary viscometer